Development of Science Teaching Materials Integrated with Islamic Values to Improve Science Learning Outcomes - Abdul Kosim (Jurnal Penelitian Pendidikan IPA, 2024)
The aims of the research were to develop instructional materials for science integrated with Islamic values, to determine the appropriateness and the effectiveness of the developed product for increasing learning output. Science learning output is consisting of attitude (religious attitudes and positive attitudes toward science) and learning achievement. This research is Research and Development (R&D) using the Borg & Gall model. Data analysis techniques using gain score, independent t-test, and MANOVA test. Instructional materials in the form of MTs student books and MTs teacher books. Product assessment of the MTs student books according to matter experts and media experts are categorized "very well". The MTs teacher books according to matter experts are categorized "good", and according to media experts are categorized "very well". Learning to use student books showed that religious attitudes had risen high (the mean gain score was 0.70), positive attitudes towards science had risen middle (the mean gain score was 0.57), and science learning achievement had risen middle (the mean gain score was 0.55). MANOVA test showed that Sig value is 0.00.